Rural Economy in Ulyanovsk Region in Early 1950s - R. A. Mukhamedov; A. V. Savelyev (Научный диалог)
This article explores the development of agriculture in the Ulyanovsk region during the early 1950s. It examines the role of machine-tractor stations (MTS) in the operation of the collective farming production system. The study pays particular attention to the material and technical condition of the MTS. An analysis of the dynamics of labor resources in rural areas is conducted. The work of party structures in staffing collective farms and machine-tractor stations in the Ulyanovsk region is analyzed, including efforts to improve training conditions in vocational and technical education institutions and the establishment of specialized courses at MTS for the training of mechanizers and enhancement of their technical skills. The article evaluates the outcomes achieved by regional collective farms in livestock and crop production. Factors that hindered the full realization of planned targets are identified. The study concludes that the Ulyanovsk region, through a comprehensive set of measures, was able to effectively address the issue of preparing specialists for collective farms and machine-tractor stations, successfully fulfilling the party's directive on crop production procurement. However, it is demonstrated that the region failed to resolve issues related to mass livestock mortality, resulting in an inability to meet livestock product procurement targets.